The Extracts of Some Marine Invertebrates and Algae Collected off the Coast Waters of Vietnam Induce the Inhibitory Effects on the Activator Protein-1 Transcriptional Activity in JB6 Cl41 Cells - S. N. Fedorov; V. B. Krasokhin; L. K. Shubina; S. A. Dyshlovoy; N. H. Nam; C. V. Minh (Journal of Chemistry)
It has previously been shown that inhibition of the transcriptional activity of the oncogenic nuclear factor AP-1 can result in cancer prevention. Marine invertebrates and alga are a rich source of natural compounds that possess various biological activities. The inhibitory effects of the extracts of Vietnamese marine organisms in relation to the AP-1 transcriptional activity were examined by the luciferase method using JB6 Cl41 cells stably expressing a luciferase reporter gene controlled by AP-1 DNA binding sequence. As was found, 71 species of marine sponges out of 148 species studied contain inhibitors of the AP-1 transcriptional activity. Therefore, marine organisms as a source of biologically active compounds have a great potential for isolation of the new cancer preventive compounds that inhibit the oncogenic AP-1 nuclear factor.